PELAKSANAAN PERLINDUNGAN ANAK YANG TEREKSPLOITASI SECARA EKONOMI OLEH PEMERINTAH KOTA PADANG - Simbolon, Laurensius Arliman (Faculty of Law, Parahyangan Catholic University, 2016)
Children are our future and in their own time bear the responsibility to develop their own world. To enable them doing so, they should not be forced to work to earn a living or support their family. Children should be allowed to grow in the safety of a home, at school and at playgrounds. In this paper the author will explore children problems related economic exploitations, what policies are developed by the municipal government of Padang to protect children from economic exploitations and what are the obstacles in implementing these policies. One of the finding is that the Social and Manpower Service and the Family Planning, Women and Community Empowerment Board of the Padang municipal government develops training programs aiming to give exploited children practical skills in helping them to cope. Factors influencing economic exploitation of children are numerous and complex: lack of education, lessening of people’s adherence to religious norms, societal environment, shift in cultural values, economic problems, etc. Based on the above the author suggests that the municipal government should take cognizance of these factors when attempting to deal with the problem. Keywords: child, exploitation, economy, protection